Akkermansia muciniphila ONE effectively ameliorates dextran sulfate sodium (DSS)-induced ulcerative colitis in mice - Hongyan Zhang; Yue Pan; Ying Jiang; Mengling Chen; Xin Ma; Xueping Yu; Dayong Ren; Bin Jiang (npj Science of Food, 2024)
Abstract Akermansia muciniphila shows promise as a next-generation probiotic, however, its beneficial regulatory effects on mice ulcerative colitis (UC) has not been extensively investigated. We used an Akkermansia muciniphila strain (AKK ONE) isolated from healthy human feces to study its effect on DSS-induced colitis in mice. Our results demonstrate that AKK ONE supplementation significantly improves food intake, weight, colon length, disease activity index (DAI) score, organ index, and tissue damage of colitis mice. AKK ONE notably improved intestinal barrier integrity by significantly enhancing expression of occludin and claudin-1. Additionally, AKK ONE reduced inflammation by down-regulating IL-1β, IL-6, and TNF-α, and up-regulating IL-10. In addition to reducing excessive inflammation, AKK ONE also increased the abundance of Akkermansia and decreased the abundance of Bacteroides. Furthermore, the AKK ONE intervention markedly increased SCFAs in cecal contents. AKK ONE may be a potential therapeutic agent for improving UC, based on the findings of this study.